ANALISIS KESIAPAN GURU MENGIMPLEMENTASIKAN ASESMEN AUTENTIK DALAM KURIKULUM MERDEKA BELAJAR - Cholifah Tur Rosidah (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
Assessment, authentic can be used with the application of the Free Learning Curriculum. This article describes the readiness of teachers to implement authentic assessment in the Free Learning Curriculum which includes preparation, implementation, and analysis and reporting of assessment results. The purpose of writing is to present a factual picture of the readiness of teachers in implementing the Merdeka Learning curriculum related to authentic assessment. Writing articles is done using descriptive methods through literature study. The article was made based on problems experienced by teachers as revealed through a Focus Group Discussion (FGD) conducted during the Teacher Group Work which involved 50 teachers in Gondang Mojokerto, East Java. The results of the FGD indicated that teachers experienced various problems related to the implementation of authentic assessments, including (1) the assumption that authentic assessment was too complicated because they had to make rubrics and then convert them before inputting into the list of scores; (2) difficulty in sorting and distributing scores if one rubric includes several lessons; (3) there has been no training specifically carried out for making authentic assessment plans. The results of the study carried out accompanied by short interviews with several teachers showed that theoretically the teacher was quite ready and sufficiently understood the nature of authentic assessment. However, in practice, teachers still need a lot to learn so that they are more skilled and easier to apply. So it can be said that the teacher is not ready to apply authentic assessments, because the assessments carried out still seem improper in accordance with the rubrics available in the teacher's book. There has not been any development of an assessment rubric that may be needed to assess other skills students need.